Charqui meats are hurdle technology meat products - Shimokomaki, M.; Franco, B. D. G. M.; Biscontini, T. M.; Pinto, Marcos Franke [UNESP]; Terra, N. N.; Zorn, T. M. T. (Taylor & Francis, 1998)
Charqui meat is a tropical intermediate meat product formulated using hurdle technology, a concept described by Leistner (1,2). Salt, sodium nitrite, dehydration, and packaging are hurdles sequentially applied to inhibit deteriorating microorganisms with the possibility of selecting desirable microbiota. This would characterize charqui and its derivatives as fermented meat products. This paper reviews biochemical, physico-chemical, and ultrastructural changes that occur during processing of charquis.
Keywords: Microbiota